Soil Phosphorus Storage Capacity for Environmental Risk Assessment - Vimala D. Nair; Willie G. Harris (Advances in Agriculture)
Reliable techniques must be developed to predict phosphorus (P) storage and release from soils of uplands, ditches, streams, and wetlands in order to better understand the natural, anthropogenic, and legacy sources of P and their impact on water quality at a field/plot as well as larger scales. A concept called the “safe” soil phosphorus storage capacity (SPSC) that is based on a threshold phosphorus saturation ratio (PSR) has been developed; the PSR is the molar ratio of P to Fe and Al, and SPSC is a PSR-based calculation of the remaining soil P storage capacity that captures risks arising from previous loading as well as inherently low P sorption capacity of a soil. Zero SPSC amounts to a threshold value below which P runoff or leaching risk increases precipitously. In addition to the use of the PSR/SPSC concept for P risk assessment and management, and its ability to predict isotherm parameters such as the Langmuir strength of bonding, KL, and the equilibrium P concentration, EPC0, this simple, cost-effective, and quantitative approach has the potential to be used as an agronomic tool for more precise application of P for plant uptake.